Rift Valley fever vaccines: an overview of the safety and efficacy of the live-attenuated MP-12 vaccine candidate - Tetsuro Ikegami (Taylor & Francis Group, 2017)
Introduction: Rift Valley fever (RVF) is a mosquito-borne zoonotic viral disease endemic to Africa and the Arabian Peninsula. High rates of abortion among infected ruminants and hemorrhagic fever in infected humans are major public health concerns. Commercially available veterinary RVF vaccines are important for preventing the spread of the Rift Valley fever virus (RVFV) in endemic countries; however, RVFV outbreaks continue to occur frequently in endemic countries in the 21st century. In the U.S., the live-attenuated MP-12 vaccine has been developed for both animal and human vaccination. This vaccine strain is well attenuated, and a single dose induces neutralizing antibodies in both ruminants and humans. Areas covered: This review describes scientific evidences of MP-12 vaccine efficacy and safety, as well as MP-12 variants recently developed by reverse genetics, in comparison with other RVF vaccines. Expert commentary: The containment of active RVF outbreaks and long-term protection from RVF exposure to infected mosquitoes are important goals for RVF vaccination. MP-12 vaccine will allow immediate vaccination of susceptible animals in case of an unexpected RVF outbreak in the U.S., whereas MP-12 vaccine may be also useful for the RVF control in endemic regions.